2019
DOI: 10.7554/elife.44345
|View full text |Cite
|
Sign up to set email alerts
|

ADAM17-dependent signaling is required for oncogenic human papillomavirus entry platform assembly

Abstract: Oncogenic human papillomaviruses (HPV) are small DNA viruses that infect keratinocytes. After HPV binding to cell surface receptors, a cascade of molecular interactions mediates the infectious cellular internalization of virus particles. Aside from the virus itself, important molecular players involved in virus entry include the tetraspanin CD151 and the epidermal growth factor receptor (EGFR). To date, it is unknown how these components are coordinated in space and time. Here, we studied plasma membrane dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 76 publications
(139 reference statements)
3
36
0
Order By: Relevance
“…In control cells, PsVs reduce the CD151 level by ≈20% ( Fig. 6B), confirming the idea that CD151 in the basal membrane is reduced upon PsV incubation 5,28 . In the integrin α6 knockdown, PsV-binding is decreased by ≈55% ( Fig.…”
Section: Figuresupporting
confidence: 78%
See 2 more Smart Citations
“…In control cells, PsVs reduce the CD151 level by ≈20% ( Fig. 6B), confirming the idea that CD151 in the basal membrane is reduced upon PsV incubation 5,28 . In the integrin α6 knockdown, PsV-binding is decreased by ≈55% ( Fig.…”
Section: Figuresupporting
confidence: 78%
“…In a recent study, integrin α3 was shown to be directly involved in EGFR signalling 58 ; this can be connected to a report showing that ADAM17-mediated EGFR signalling is involved in HPV entry platform formation and infection. Here, cell surface CD151 association with viral particles was dependent on EGFR mediated signalling 28 . Hence, integrin α3 may be required to sustain EGFR signalling as a prerequisite for HPV internalization.…”
Section: Scientific Reports |mentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, it has been well established that CD9 also regulates the function of cell membrane proteases including ADAM17 [28,30,31,33]. ADAM17, in turn, triggers ERK signalling which is important for HPV16 entry receptor formation [12]. Therefore, we speculated that CD9 affects HPV infection by modulating ADAM17 activity and thus analysed the spatial distribution and association of the two plasma membrane proteins in HeLa cells (Fig.…”
Section: A Specific Cd9 Optimum Promotes Adam17 Activity and Erk Signmentioning
confidence: 99%
“…Here, heparan sulphate proteoglycans and laminins are identified as attachment receptors [6,7]. Subsequent virus entry into the infectious pathway requires signalling processes [8][9][10][11][12] and virus association with secondary entry receptor molecules including tetraspanin CD151 [12][13][14], integrin complexes [14,15], growth factor receptors (GFRs) [11,12], and the phospholipidbinding protein annexin A2 [16,17]. We have previously uncovered that not only CD151 but also additional tetraspanin family members, tetraspanin CD63 [18] and CD9 [19], act as proviral host-cell factors in HPV16 infection and that the cellular protease "A Disintegrin And Metalloprotease 17" (ADAM17), triggers the assembly of the HPV16 entry platform by modulating the extracellular signal-regulated kinases (ERK1/2) signalling pathway [12].…”
Section: Introductionmentioning
confidence: 99%